Dietary shift in the American Kestrel under severe drought conditions in the southern Baja California Peninsula - Martín G. Frixione; Christian Salvadeo; Hugo Alfredo Juárez-Castañón; Sergio Ivan Santana-Rodriguez; Georgina Brabata-Domínguez (Food Webs, 2026)

Which soil health indicators best track diversification benefits in tropical agroecosystems? - Anna M. Visscher; Simon Fonteyne; Mirjam Pulleman; Anna Alekseeva; Martin Hartmann; Jose M. Rodriguez-Castellanos; Pankaj Trivedi; Rodolfo Vilchis-Ramos; Sergio Zapata-Martínez; Bruce G. Ferguson; Helda Morales; Steven Vanek; et al. (Applied Soil Ecology, 2026)

Frequency matters: multi-year late-spring frosts severely reduce growth resilience of Nothofagus pumilio near Tierra del Fuego treeline - Sergio Piraino; Vladimir Matskovsky; Paolo Cherubini; Martín Ariel Hadad; Guillermo Martínez Pastur; Julián Rodriguez-Souilla; Fidel Alejandro Roig Juñent (Acta Oecologica, 2026)

Hybrid Sparrow Search Algorithm Support Vector Machine Regression Bidirectional Long-Short Term Memory (SSA-SVR-BiLSTM) model with Lagrange-based weighting for PM$$_{2.5}$$ prediction and stratified evaluation - Maria Fernanda Camargo; Sergio Diaz; Ricardo Elias Celis Parra; Vladimir Ramírez Tarazona; Astrith Eugenia Rincón Sánchez; V. Rodriguez-Rueda; Omar F. Rojas-Moreno; Alejandra Baena (Environmental and Ecological Statistics, 2026)
Air pollution is a major environmental risk to public health, strongly associated with cardiovascular and respiratory diseases. According to the World Health Organization, at least 99% of the global population lives in areas that do not meet its air-quality guidelines. PM $$_{2.5}$$ 2.5 variability reflects the interaction between local emission sources and meteorological processes that regulate near-surface dispersion and accumulation, producing nonlinear temporal patterns that motivate hybrid modeling approaches. We propose an SSA-SVR-BiLSTM framework for short-term PM $$_{2.5}$$ 2.5 forecasting that combines SSA-optimized SVR and BiLSTM models within a constrained linear ensemble with weights estimated exclusively on the validation partition using Lagrange multipliers. The model is evaluated on 10 months of high-frequency (5-min) air-quality and meteorological data collected at a traffic-influenced monitoring site in Duitama, Colombia. On the held-out test set, the hybrid achieved $$R^2 = 0.9585$$ R 2 = 0.9585 and MAPE $$= 7.62%$$ = 7.62 % , outperforming five of six SSA-optimized baselines; the difference relative to the best individual model (SSA-SVR was statistically significant but practically negligible ( $$p = 0.0105$$ p = 0.0105 , $$Δ R^2 = 0.0002$$ Δ R 2 = 0.0002 ), and the value of the hybrid lies primarily in its improved consistency across low and medium concentration regimes rather than in a large global accuracy gain. Stratified evaluation across concentration regimes and normative thresholds (WHO, EPA) revealed systematic underestimation at extreme pollution episodes, a structural limitation shared by all evaluated models. A feature occlusion analysis identified PM $$_5$$ 5 and PM $$_{10}$$ 10 as the dominant exogenous predictors (53.6 and 21.7%), with meteorological variables contributing an additional $${\sim }20%$$ ∼ 20 % of the total relevance.

Development of conventional and quantitative PCR assays for the detection of Vibrio europaeus using a Species-Specific gene identified from the pangenome - Diego Rey-Varela; Ana L. Diéguez; Sergio Rodriguez; Ezgi Dinçtürk; Antia Villada; Justa Ojea; David Polo; Javier Dubert (Journal of Invertebrate Pathology, 2026)

Uncovering how major extracellular proteins drive virulence and functional compensation in the mollusk pathogen Vibrio europaeus - Clara Martínez; Sergio Rodriguez; Alba Trueba; Diego Rey-Varela; Alicia E. Toranzo; Ana L. Dieguez; Javier Dubert (Journal of Invertebrate Pathology, 2026)

Bioactive Extracts from Yucatán Marine Invertebrates as Modulators of Microalgal Dynamics - Dawrin Pech-Puch; Rita Pires; Bárbara A. Rebelo; Diana Grilo; Carlos Gonzáles-Salas; Susana Eunice Calva-Pérez; Susana M. Gomes; Harold Villegas-Hernández; Sergio Guillén-Hernández; Abel M. Forero; Jaime Rodriguez; Carlos Jiménez; et al. (Marine Biotechnology, 2026)
The marine environment is a rich source of bioactive compounds with a wide range of applications. In this study, 65 extracts from sponges, ascidians, and a gorgonian collected from the Yucatán Peninsula, Mexico, were evaluated for their modulatory effects on the growth of four microalgal species. Some extracts were found to exhibit pronounced algicidal activity, while others promoted growth. Bioassay-guided fractionation of the extract from Haliclona (Rhizoniera) curacaoensis led to the identification of arenosclerins A and C as potent algicidal agents, active across all tested microalgae. In contrast, the extract from Halichondria melanadocia enhanced microalgal growth, and chemical analysis revealed the presence of medelamine A and B as putative growth-promoting compounds. This study provides a new report on microalgae-modulating activities of marine sponge metabolites. The dual activity observed, both inhibitory and stimulatory, not only contributes to our understanding of marine compound diversity but also underscores the potential of these marine-derived compounds for sustainable environmental management practices.

Climatic Niche Modelling Reveals Limited Phylogenetic Niche Conservatism in New World Crocodylians - Andrés L. Rodriguez‐Cordero; Nancy E. McIntyre; Richard D. Stevens; Joseph D. Manthey; Carlos Portillo‐Quintero; Natasja Van Gestel; Sergio A. Balaguera‐Reina; Brandon A. Gross; Margaret Munn; Llewellyn D. Densmore (Journal of Biogeography, 2026)
Aim Phylogenetic niche conservatism, the tendency of closely related species to retain ancestral ecological traits, has gained considerable interest, yet the lack of integration across independent evaluation methods has hindered our understanding of whether niches are conserved or dynamic. Such an understanding is especially relevant for taxa of conservation concern, such as crocodylians (order Crocodylia). This study assessed niche conservatism among New World crocodylians by combining ensemble species distribution models, phylogenetics, and standard metrics of geographic and environmental niche overlap. Location America. Major Taxa Order Crocodylia. Methods We estimated species' climatic niches in geographic and environmental dimensions to assess overlap patterns and quantified associations between niche overlap and phylogenetic patristic distance using the Mantel test and phylogenetic independent contrast (PIC). Results Overlap analyses in geographic and environmental spaces revealed climatic niche differentiation across the clade, suggesting divergent environmental preferences among species. The relationship between phylogenetic patristic distance and climatic niche overlap assessed via Mantel tests revealed a significant negative correlation with geographic niche overlap ( ρ = −0.361, p = 0.005), but no evidence for associations with environmental niche overlap (Schoener's D: ρ = −0.079, p = 0.184; Hellinger's I: ρ = −0.063, p = 0.250), suggesting that more distantly related species overlap less geographically. In contrast, the relationship assessed using PIC revealed no evidence for associations between phylogenetic distance and either geographic ( ρ = −0.200, p = 0.579) or environmental niche overlap (D: ρ = −0.294, p = 0.41; I: ρ = −0.319, p = 0.369). Conclusions We found no strong or consistent evidence for phylogenetic conservatism in climatic niches across both geographic (inverse relationship) and environmental (no relationship) dimensions in New World crocodylians. This study enhances our understanding of niche dynamics and highlights the value of integrating niche modelling with phylogenetic analyses to detect biogeographic and evolutionary patterns.

From potato peels to power: Evaluation and scale-up simulation of hydrochar as catalyst for water splitting - Aida M. Díez; Miguel A. Rodriguez; Adrián Cabarcos; Sergio Chapela; M.Ángeles Sanromán; Marta Pazos (Fuel, 2026)

Acute pancreatic panniculitis in a domestic ferret (Mustela putorius furo): diagnostic insights and a potential drug-induced etiology - Jacobo Giner; José Villora; Carles Juan-Sallés; Ana Rodriguez-Largo; Álex Gómez; Sergio Villanueva-Saz; Diana Marteles (Veterinary Research Communications, 2026)
Panniculitis is a rare condition in ferrets ( Mustela putorius furo ), previously linked to nutritional deficiencies, infections, trauma, and injections. Pancreatic panniculitis, caused by the systemic release of pancreatic enzymes during pancreatic injury, has been documented in humans and other animal species, but not in ferrets. This report describes the first known case in a domestic ferret. A 2-year-old male ferret presented with ulcerated cutaneous nodules predominantly affecting the hind limbs and inguinal abdominal region. The ferret had been treated with rifampicin and clarithromycin for suspected mycobacterial infection. Hyperglycemia, hyperglobulinemia, and elevated alkaline phosphatase were noted. Cytology and culture of the lesions revealed neutrophilic inflammation and Pseudomonas aeruginosa , respectively. The animal developed acute abdominal discomfort and died shortly after. Post-mortem examination revealed severe pancreatic necrosis and peripancreatic panniculitis, with splenic pyogranulomatous inflammation. Immunohistochemistry detected systemic coronavirus antigen (clone FCV3-70) only in the spleen. In this patient, prolonged use of rifampicin and clarithromycin is considered a potential contributing factor to the development of acute pancreatic necrosis. This case highlights the clinical relevance of pancreatic panniculitis in ferrets and suggests a possible association between extended rifampicin/clarithromycin therapy and pancreatic necrosis. Ultrasonography and serum glucose, lipase, and amylase measurements are recommended for early diagnosis. Histopathological evaluation remains essential for confirmation.

High frequency of plastic-derived contaminants (phthalate acid esters) in the preen gland of dead procellariiform seabirds from the Patagonian Sea - Luciana Gallo; María Rosa Repetti; Melina Paola Michlig; Leandro L. Tamini; Leandro N. Chavez; Ruben F. Dellacasa; C. Karina Alvarez; Sergio A. Rodriguez Heredia; Ralph Eric Thijl Vanstreels; Patricia Pereira Serafini; Marcela M. Uhart (Marine Pollution Bulletin, 2026)

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

Optical and random laser properties of the novel multifunctional endoxifen derivative (FLTX3) and its potential for the diagnosis of breast cancer resistance - Mario Diaz; Sergio de Armas-Rillo; Fernando Lobo; Daniel Pereda de Pablo; Kevin Soler-Carracedo; Pablo Delgado; Mitzi Rodriguez; Ana Canerina-Amaro; Catalina Valdes-Baizabal; Raquel Marín; Dácil Hernández; Alicia Boto; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Cocaine Use Disorder: Neuropathology and Exploratory Treatments - Amanda Almeida; Halford G. Warlick; Arisha Arain; Simran Arora; Erick Boldt; Causicaa Chandramohan; Prathmica Chandramohan; Maiah Fogel; Hamid Gogerdchian; Borna Hajivandi; Armena Jafarmadar; Marianne Koleng; et al. (Molecular Neurobiology, 2026)

The MiniBond test: A robust and cost-effective alternative for ore hardness characterisation and geometallurgical profiling - Diego Mesa; Patricio Berríos; Esteban Rodriguez; Caillan Govender; Portia Mudau; Sergio Spichiger; Roger Amelunxen; Peter Amelunxen (Minerals Engineering, 2025)

A comprehensive analysis of the nitrogen synchrony between cover crops release and maize uptake - Walter D. Carciochi; Francisco Cafaro La Menza; Denis G. Terwissen Gjerloff; Nahuel I. Reussi Calvo; Guillermo A. Divito; Oscar R. Avila Manotoa; María P. Rodriguez; Sergio Tovar Hernández; Adrian M. Lapaz Olveira; Hernán R. Sainz Rozas; Pablo A. Barbieri (Plant and Soil, 2025)

Time-dependent post-mortem histomorphological changes in Penaeus vannamei following humane euthanasia - Rodolfo Lozano-Olvera; Karla G. Aguilar-Rendón; Sergio Cervantes; Selene M. Abad-Rosales; Sonia A. Soto-Rodriguez; María C. Chávez-Sánchez (Veterinary Research Communications, 2025)

Insecticidal and repellent properties of Baccharis salicifolia essential oil against the stored product pest of Neltuma alba, Riphibruchus picturatus (F.) (Coleoptera: Chrysomelidae: Bruchinae): Chemical composition and mechanism of action - Valeria Tapia Mattar; Axel Hollmann; Sergio A. Rodriguez (South African Journal of Botany, 2025)

A machine learning approach for type 2 diabetes diagnosis and prognosis using tailored heterogeneous feature subsets - J. Ramón Navarro-Cerdán; Pedro Pons-Suñer; Laura Arnal; Joaquim Arlandis; Rafael Llobet; Juan-Carlos Perez-Cortes; Francisco Lara-Hernández; Celeste Moya-Valera; Maria Elena Quiroz-Rodriguez; Gemma Rojo-Martinez; Sergio Valdés; Eduard Montanya; et al. (Medical & Biological Engineering & Computing, 2025)
Type 2 diabetes (T2D) is becoming one of the leading health problems in Western societies, diminishing quality of life and consuming a significant share of healthcare resources. This study presents machine learning models for T2D diagnosis and prognosis, developed using heterogeneous data from a Spanish population dataset (Di@bet.es study). The models were trained exclusively on individuals classified as controls and undiagnosed diabetics, ensuring that the results are not influenced by treatment effects or behavioral changes due to disease awareness. Two data domains are considered: environmental (patient lifestyle questionnaires and measurements) and clinical (biochemical and anthropometric measurements). The preprocessing pipeline consists of four key steps: geospatial data extraction, feature engineering, missing data imputation, and quasi-constancy filtering. Two working scenarios (Environmental and Healthcare) are defined based on the features used, and applied to two targets (diagnosis and prognosis), resulting in four distinct models. The feature subsets that best predict the target have been identified based on permutation importance and sequential backward selection, reducing the number of features and, consequently, the cost of predictions. In the Environmental scenario, models achieved an AUROC of 0.86 for diagnosis and 0.82 for prognosis. The Healthcare scenario performed better, with an AUROC of 0.96 for diagnosis and 0.88 for prognosis. A partial dependence analysis of the most relevant features is also presented. An online demo page showcasing the Environmental and Healthcare T2D prognosis models is available upon request. Graphic abstract

A European survey on anaerobes from paediatric blood cultures: a comparative analysis with adults - Matteo Boattini; Arianna Aceti; Paulo Bastos; Viktoria Eirini Mavromanolaki; Sofia Maraki; Anastasia Spiliopoulou; Vasileios Kakouris; Yordan Kalchev; Ana Budimir; Branka Bedenić; Zana Rubic; Monica Licker; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Correction to: Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández‑Pérez; Joan Jiménez‑Balado; Adrià Macias‑Gómez; Antoni Suárez‑Pérez; Marta Vallverdú‑Prats; Alberto Pérez‑Giraldo; Marc Viles‑García; Julia Peris‑Subiza; Sergio Vidal‑Notari; Eva Giralt‑Steinhauer; Daniel Guisado‑Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández-Pérez; Joan Jiménez-Balado; Adrià Macias-Gómez; Antoni Suárez‑Pérez; Marta Vallverdú-Prats; Alberto Pérez-Giraldo; Marc Viles-García; Julia Peris-Subiza; Sergio Vidal-Notari; Eva Giralt-Steinhauer; Daniel Guisado-Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

Biomass Valorization of Unexplored Canara and Capiaçu Elephant Grass Cultivars for Pyrolytic Sugar (Levoglucosan) Production via Fast Pyrolysis - Thays da Costa Silveira; Euripedes Garcia Silveira Junior; Victor Haber Perez; Geraldo Ferreira David; Sergio Antonio Fernandes; Oselys Rodriguez Justo; Carina Aline Prado; Júlio César dos Santos (BioEnergy Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Insomnia accelerates the epigenetic clocks in older adults - Nadia Alejandra Rivero-Segura; Julian Daniel Rodriguez Cuartas; Paola Garcia-delaTorre; Sergio Sanchez-Garcia; Ricardo Ramirez-Aldana; Juan Carlos Gomez-Verjan (GeroScience, 2025)

Capped honey segmentation in honey combs based on deep learning approach - Francisco J. Rodriguez-Lozano; Sergio R. Geninatti; José M. Flores; Francisco J. Quiles-Latorre; Manuel Ortiz-Lopez (Computers and Electronics in Agriculture, 2024)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Fouling and scaling in reverse osmosis desalination plants: A critical review of membrane autopsies, feedwater quality guidelines and assessment methods - Marc Philibert; Loreen O. Villacorte; Yuli Ekowati; Almotasembellah Abushaban; Sergio G. Salinas-Rodriguez (Desalination, 2024)

Comparative analysis of eleven SARS-CoV-2 immunoassays and neutralisation data: time to enhance standardisation and correlation of protection - Jorge-Julio Cabrera-Alvargonzalez; Carlos Davina-Nunez; Sonia Rey-Cao; Leticia Rodriguez Calviño; Sergio Silva-Bea; Elena Gonzalez-Alonso; Raquel Carballo-Fernandez; Carmen Lameiro Vilariño; Sandra Cortizo-Vidal; Pilar Valiño-Prieto; Miriam Rodriguez-Perez; Sonia Pérez Castro; et al. (Infectious Diseases, 2024)

Geotechnologies on the phosphorus stocks determination in tropical soils: General impacts on society - Jorge Tadeu Fim Rosas; José A.M. Demattê; Nícolas Augusto Rosin; Bruno dos Anjos Bartsch; Raul Roberto Poppiel; Heidy Soledad Rodriguez-Albarracin; Jean Jesus Macedo Novais; Paulo Sergio Pavinato; Yuxin Ma; Danilo César de Mello; Marcio Rocha Francelino; Marcelo Rodrigo Alves (Science of The Total Environment, 2024)

Correction: Tick-Borne Pathogens Screening Using a Multiplex Real-Time Polymerase Chain Reaction-Based Method - Sergio Andres Cardenas-Cadena; Maria Eugenia Castañeda-Lopez; Fabiana Esther Mollinedo-Montaño; Sodel Vazquez-Reyes; Jorge Lara-Arias; Ivan Alberto Marino-Martinez; Iram Pablo Rodriguez-Sanchez; Idalia Garza-Veloz; Margarita L. Martinez-Fierro (Acta Parasitologica, 2024)

Insecticidal action, repellency, and toxicity mechanism of the essential oil of Lippia turbinata against the stored product pest Rhipibruchus picturatus (F.) - Valeria Tapia Mattar; José Luis Borioni; Axel Hollman; Sergio A. Rodriguez (Pesticide Biochemistry and Physiology, 2024)

GrimAge is elevated in older adults with mild COVID-19 an exploratory analysis - Paola García-delaTorre; Nadia Alejandra Rivero-Segura; Sergio Sánchez-García; Kristhian Becerril-Rojas; Francisco Ernesto Sandoval-Rodriguez; Diana Castro-Morales; Miguel Cruz-Lopez; Miguel Vazquez-Moreno; Ruth Rincón-Heredia; Perla Ramirez-Garcia; Juan Carlos Gomez-Verjan (GeroScience, 2024)

The uneven burden of COVID-19 in the metropolitan region of São Paulo, Brazil – Risk analysis from a bottom-up perspective - Alexandre Pereira Santos; Katharina Heider; Sergio Gresse Junior; Juan Miguel Rodriguez Lopez (Applied Geography, 2024)

Simultaneous improvement of grain yield and grain protein concentration in durum wheat by using association tests and weighted GBLUP - Salvatore Esposito; Paolo Vitale; Francesca Taranto; Sergio Saia; Ivano Pecorella; Nunzio D’Agostino; Monica Rodriguez; Vincenzo Natoli; Pasquale De Vita (Theoretical and Applied Genetics, 2023)

Design recommendations for the rehabilitation of an urban canyon in a subtropical climate region using aerial thermography and simulation tools - Marta Videras Rodriguez; Sergio Gomez Melgar; Jose Manuel Andujar Marquez (Energy and Buildings, 2023)

Tick-Borne Pathogens Screening Using a Multiplex Real-Time Polymerase Chain Reaction-Based Method - Sergio Andres Cardenas-Cadena; Maria Eugenia Castañeda-Lopez; Fabiana Esther Mollinedo-Montaño; Sodel Vazquez-Reyes; Jorge Lara-Arias; Ivan Alberto Marino-Martinez; Iram Pablo Rodriguez-Sanchez; Idalia Garza-Veloz; Margarita L. Martinez-Fierro (Acta Parasitologica, 2023)
Purpose This study aims to develop and evaluate a cost-effective, user-friendly multiplex quantitative real-time polymerase chain reaction (qPCR) method for detecting multiple tick-borne pathogens associated with human and veterinary diseases. Methods In silico PCR was performed to design and evaluate primer sequences reported for amplifying Rickettsia spp ., Borrelia spp. , and Ehrlichia spp. Single and multiplex qPCR assays were then standardized to detect individual pathogens and multiple pathogens in a single reaction. Positive controls were generated to determine the dynamic range of the methods. In the validation phase, a total of 800 samples were screened for the presence of tick-borne pathogens. Results Identification in a single qPCR reaction (multiplex) of Ehrlichia spp . , and Borrelia spp. with a limit of detection of 10 copies and Rickettsia spp . with 100 copies, a PCR efficiency (E) of 90–100% and a coefficient of correlation ( R 2 ) of 0.998–0.996 for all pathogens. Conclusion The ability to detect three significant pathogens (Ehrlichia spp ., Rickettsia spp ., and Borrelia spp .) in a single qPCR reaction offers a significant advantage in the field of molecular diagnostics for tick-borne diseases. This advancement has a profound impact on public health as it facilitates the selection of appropriate treatment protocols, thereby reducing complications associated with disease progression. The streamlined approach provided by this method simplifies the diagnostic process and enables timely intervention, ultimately improving patient outcomes and mitigating the potential risks associated with untreated or misdiagnosed tick-borne infections.

Mechanistic insight into the synthesis of fucooligosaccharides by α-L-fucosidase from Thermotoga maritima belonging to the GH29 family: in silico study - Mauricio E. Pavón-Chimal; Carlos Jiménez-Pérez; Francisco Guzmán-Rodriguez; Sergio Alatorre-Santamaría; Luis G. González-Olivares; Mariano García-Garibay; Lorena Gómez-Ruiz; Gabriela Rodríguez-Serrano; Alma E. Cruz-Guerrero (Biologia, 2022)

Diagnosis of bacterial meningitis caused by Streptococcus pneumoniae, Neisseria meningitidis, and Haemophilus influenzae using a multiplex real-time PCR technique - María Noemí Carnalla-Barajas; Araceli Soto-Noguerón; Lucila Martínez-Medina; Maria Elizabeth Olvera-Herrera; Juan Luis Mosqueda-Gómez; Patricia Rodríguez-Cortez; Rayo Morfin-Otero; Eduardo Rodriguez-Noriega; Antonio Luévanos-Velázquez; Mariana Merlo-Palomera; Sergio Esparza-Ahumada; Francisco Márquez-Díaz; et al. (Brazilian Journal of Microbiology, 2022)

Ataxia Myoclonus Syndrome in Mild Acute COVID-19 Infection - Sergio Rodriguez-Quiroga; Mayra Aldecoa; Nicolas Morera; Carolina Gatti; Cesar Gil; Nélida Garretto; Alfonso Fasano (The Cerebellum, 2022)

Geophysical reconnaissance of the western basin of the Plaine du Nord aquifer, Haiti - Wm. Javan Miner; James K. Adamson; James C. Hasbrouck; Sergio Perez Monforte; María Rodriguez Vera (Hydrogeology Journal, 2022)
A geophysical reconnaissance was conducted to support aquifer characterization and evaluate groundwater potential in the western portion of the Plaine du Nord aquifer to provision the growing water demands of the city of Cap-Haitien in the Republic of Haiti. Hybrid-source audio-magnetotelluric (HSAMT) soundings and gravity measurements were collected to support the Government of Haiti in sourcing additional water supplies for the city. The Plaine du Nord aquifer is poorly characterized considering it is one of Haiti’s largest aquifers, few drilling logs are available, and only one borehole has investigated the deeper extents of the aquifer. HSAMT supports depth profiling of subsurface resistivity, which supports interpretations of geological strata and groundwater conditions. Gravity measurements allow for complementary mapping of Earth density anomalies and contrasts, which assist in interpreting aquifer thicknesses or depth to bedrock. Pairing HSAMT and gravity methods permitted both an estimation of aquifer thickness and relative changes in sediment characteristics. Gravity results allowed for the mapping of aquifer thickness across the study area, with interpreted thickness greater than 300 m in the coastal zone. HSAMT results cross correlated with available well records and enabled the delineation of zones with increased groundwater potential. The results of the combined methods indicate groundwater storage potential of freshwater in deeper alluvium and emphasize the importance of strengthening resource characterization, modelling and monitoring to guide sustainable resource development and management.

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Shrimp immune response: A transcriptomic perspective - Carlos Fajardo; Gonzalo Martinez‐Rodriguez; Benjamin Costas; Juan Miguel Mancera; Sergio Fernandez‐Boo; Hectorina Rodulfo; Marcos De Donato (Reviews in Aquaculture, 2022)
During the last 15 years, a significant amount of data related to the crustacean immune system has been generated, mainly led by the advances made in the field of transcriptomic analysis through massive mRNA sequencing technology. In order to shed new light on the genes and metabolic pathways associated with the immune system in shrimp species, we have carried out a meta‐analysis using the current literature and the Sequence Read Archive (SRA) database of the National Center for Biotechnology Information (NCBI), which has 1195 published transcriptomic data sets until 31 December 2020, from different tissues and 14 Penaeus species. The transcriptomic analyses published so far have explored the effects of the challenge from viral and bacterial pathogens, as well as abiotic stressors, such as ammonia, temperature, salinity, oxygen deprivation and pH. They have also explored the effect of dietary factors and beneficial microbes (pre‐ and probiotics) in the immune response. In order to harness the vast amount of information available, multidisciplinary efforts have to generate better genomic tools to overcome the complexity of the genome and to implement the knowledge gained into commercial applications for the improvement of the culture conditions, adaptation of more sustainable feeds and producing strains showing more resilience/tolerance to diseases.

Charismatic Species as Indicators of Plastic Pollution in the Río de la Plata Estuarine Area, SW Atlantic - Victoria González Carman; Pablo Denuncio; Martina Vassallo; María Paula Berón; Karina C. Álvarez; Sergio Rodriguez-Heredia (Frontiers in Marine Science, 2021)
Marine plastic pollution is projected to increase globally in the next few decades. This holds true for South America where the number of species that interacts with plastics is increasing. In this study, we explore for the first time the potential of certain charismatic species of marine turtles, mammals and seabirds as indicators of plastic pollution in the Río de la Plata (RdP), one of the largest and most important estuarine areas of the Southwest Atlantic. Through a revision of published studies integrated with unpublished data, we summarize studies on the interaction of charismatic marine species with plastics in the region and evaluate their role as indicators of plastic pollution in the RdP based on aspects of their local ecology and key attributes (i.e., biological/ecological, methodological, and conservation attributes) of indicator species. We found that at least 45 charismatic marine species interact –whether by ingestion or entanglement– with plastics in the region. Eight of these species were selected as potential indicators given their occurrence, probability of sampling and interaction with plastics in the RdP, namely: Chelonia mydas , Caretta caretta , Dermochelys coriacea , Pontoporia blainvillei , Arctocephalus australis , Otaria flavescens , Larus dominicanus , and Spheniscus magellanicus . The species shared some key attributes of indicator species, e.g., they are relatively well studied, but differed in critical aspects such as their home range and mobility. We discuss whether the species’ attributes are strengths or weaknesses according to the available knowledge on their ecology in the RdP, and propose a multispecies indicator of plastic pollution given that those strengths and weaknesses can be compensated among species. Monitoring plastic pollution through a combination of species would enable a better understanding of plastic pollution in this relevant area.

Chemical composition of Schinus areira essential oil and antimicrobial action against Staphylococcus aureus - Andrea C. Cutro; M. Victoria Castelli; Silvia N. López; Manuel A. Rosales; Axel Hollmann; Sergio A. Rodriguez (Natural Product Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Role of Formulation Parameters on Intravitreal Dosing Accuracy Using 1 mL Hypodermic Syringes - Christian Weinmann; Ahmad S. Sediq; Martin Vogt; Hanns-Christian Mahler; Susanne Joerg; Sergio Rodriguez; Roman Mathaes; Dhananjay Jere (Pharmaceutical Research, 2020)

Tryptophan supplementation helps totoaba (Totoaba macdonaldi) juveniles to regain homeostasis in high-density culture conditions - Miguel Cabanillas-Gámez; Ulises Bardullas; Mario A Galaviz; Sergio Rodriguez; Verónica M Rodriguez; Lus M López (Fish Physiology and Biochemistry, 2020)

Adenovirus-Mediated Transduction of Insulin-Like Growth Factor 1 Protects Hippocampal Neurons from the Toxicity of Aβ Oligomers and Prevents Memory Loss in an Alzheimer Mouse Model - Maria Clara Selles; Juliana T. S. Fortuna; Maria F. Zappa-Villar; Yasmin P. R. de Faria; Amanda S. Souza; Claudia K. Suemoto; Renata E. P. Leite; Roberta D. Rodriguez; Lea T. Grinberg; Paula C. Reggiani; Sergio T. Ferreira (Molecular Neurobiology, 2020)

Antifungal activity of Copaíba resin oil in solution and nanoemulsion against Paracoccidioides spp. - Lívia do Carmo Silva; Meire Ane Costa Miguel Miranda; Julianna Veiga de Freitas; Sarah Fernanda Araújo Ferreira; Emília Celma de Oliveira Lima; Cecilia Maria Alves de Oliveira; Lucilia Kato; Ana Paula Terezan; Anselmo Fortunato Ruiz Rodriguez; Fernando Sergio Escócio Drumond Via Faria; Célia Maria de Almeida Soares; Maristela Pereira (Brazilian Journal of Microbiology, 2020)

Evaluation of occult hepatitis B infection in tissue donors: a multicenter analysis in Spain - Jacinto Sánchez Ibáñez; Ana Vilarrodona Serrat; Teresa Seoane Pillado; Clara Rodriguez Aierbe; Rafael Villalba Montoro; Javier Calvo Benito; Marta Pevida Lopez; Sergio Fernández Paneque; Elena Vuelta Lopez; Maria Jose Martínez Lorenzo; Manuel González Romero; Angelina Cañizares Castellanos; et al. (Cell and Tissue Banking, 2019)

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

PTRF acts as an adipokine contributing to adipocyte dysfunctionality and ectopic lipid deposition - Sergio Perez-Diaz; Maria P. Garcia-Sobreviela; Yolanda Gonzalez-Irazabal; Beatriz Garcia-Rodriguez; Silvia Espina; Izaskun Arenaz; Jose M. Arbones-Mainar (Journal of Physiology and Biochemistry, 2018)

Reproductive traits and relative gonad expenditure of the sexes of the free spawning Chiton articulatus (Mollusca: Polyplacophora) - Quetzalli Yasu Abadia-Chanona; Omar Hernando Avila-Poveda; Marcial Arellano-Martinez; Bertha Patricia Ceballos-Vazquez; Francisco Benitez-Villalobos; Geoff A. Parker; Guillermo Rodriguez-Dominguez; Sergio Garcia-Ibañez (Invertebrate Reproduction & Development, 2018)

Advances in the Chemical Ecology of the Spotted Wing Drosophila (Drosophila suzukii) and its Applications - Kevin R. Cloonan; John Abraham; Sergio Angeli; Zainulabeuddin Syed; Cesar Rodriguez-Saona (Journal of Chemical Ecology, 2018)

Neurobiological Role of Hypocretin in Regulation of Psychiatric Disorders - Suzana Monteiro; Barbara Monteiro; Flavia Paes; Antônio Egídio Nardi; Nuno Rocha; Eric Murillo-Rodriguez; Sergio Machado (Sleep and Vigilance, 2018)

Genome characterization of an Argentinean isolate of alfalfa leaf curl virus - Nicolás Bejerman; Verónica Trucco; Soledad de Breuil; Patricia Rodriguez Pardina; Sergio Lenardon; Fabián Giolitti (Archives of Virology, 2018)

Degradation of Hexachlorocyclohexanes (HCHs) by Stable Zero Valent Iron (ZVI) Microparticles - Carmen M. Dominguez; Sergio Rodriguez; David Lorenzo; Arturo Romero; Aurora Santos (Water, Air, & Soil Pollution, 2016)

Microsphere-Based Rapamycin Delivery, Systemic Versus Local Administration in a Rat Model of Renal Ischemia/Reperfusion Injury - Jurjen Zandstra; Marike M. van Beuge; Johan Zuidema; Arjen H. Petersen; Mark Staal; Luisa F. Duque; Sergio Rodriguez; Audrey A. R. Lathuile; Gert J. Veldhuis; Rob Steendam; Ruud A. Bank; Eliane R. Popa (Pharmaceutical Research, 2015)

Inhibition of CaV2.3 channels by NK1 receptors is sensitive to membrane cholesterol but insensitive to caveolin-1 - Yamhilette Licon; Deniss Leandro; Catalina Romero-Mendez; Aldo A. Rodriguez-Menchaca; Sergio Sanchez-Armass; Ulises Meza (Pflügers Archiv - European Journal of Physiology, 2015)

Differential organ phenotypes after postnatal Igf1r gene conditional deletion induced by tamoxifen in UBC-CreERT2; Igf1r fl/fl double transgenic mice - Icíar Paula López; Lourdes Rodriguez-de la Rosa; Rosete Sofia Pais; Sergio Piñeiro-Hermida; Raquel Torrens; Julio Contreras; Isabel Varela-Nieto; José García Pichel (Transgenic Research, 2015)

Transducin-like enhancer of split 3 (TLE3) in adipose tissue is increased in situations characterized by decreased PPARγ gene expression - Francisco José Ortega; Marta Serrano; Sergio Rodriguez-Cuenca; José María Moreno-Navarrete; María Gómez-Serrano; Mònica Sabater; Jose Ignacio Rodriguez-Hermosa; Gemma Xifra; Wifredo Ricart; Belén Peral; Antonio Vidal-Puig; José Manuel Fernández-Real (Journal of Molecular Medicine, 2015)

Transcriptome analysis of resistant and susceptible genotypes of Glycine tomentella during Phakopsora pachyrhizi infection reveals novel rust resistance genes - Ruth Elena Soria-Guerra; Sergio Rosales-Mendoza; Sungyul Chang; James S. Haudenshield; Annamalai Padmanaban; Sandra Rodriguez-Zas; Glen L. Hartman; Said A. Ghabrial; Schuyler S. Korban (Theoretical and Applied Genetics, 2010)

Physicochemical Parameters Associated with Nanoparticle Formation in the Salting-Out, Emulsification-Diffusion, and Nanoprecipitation Methods - Sergio Galindo-Rodriguez; Eric Allémann; Hatem Fessi; Eric Doelker (Pharmaceutical Research, 2004)

A Framework for Assessment and Monitoring of Small Mammals in a Lowland Tropical Forest - Sergio Solari; Juan José Rodriguez; Elena Vivar; Paul M. Velazco (Environmental Monitoring and Assessment, 2002)

Death and neuroprotection of retinal ganglion cells after different types of injury - Manuel Vidal-Sanz; Maria Lafuente; Paloma Sobrado-Calvo; Inmaculada SellÉs-Navarro; Elena Rodriguez; Sergio Mayor-Torroglosa; MarÍa P. Villegas-PÉrez (Neurotoxicity Research, 2000)